CREATIVE TEAM STRATEGY MAINTAINING RATING AND SHARE IN THE OPERA VAN JAVA (OVJ) PROGRAM IN TRANS 7 - Muhamad Aldi Muhamad Aldi (Inter Script : Journal of Creative Communication, 2020)
ABSTRACT                    The development of the mass media industry in Indonesia makes a variety of quality programs, the information conveyed is a necessity to help the public in knowing information is happening around them. Therefore the information presented by the media must be true and useful for the wider community. Television stations broadcast programs with a variety of interesting formats, both in the form of drama programs, non-drama programs, and news programs. The characteristics of television can display images and sound to be the main factor and every television station has many programs with various formats, one of them is comedy program. Television ratings have a very long history, so television stations present programs that are very diverse and interesting. Especially programs with comedy formats such as one of the trans 7 television stations that present Opera Van Java. By adapting traditional forms of wayang performances that are packed in a more modern way, by bringing up stories / phenomena in the community. The aim is to find out the creative team's strategy to maintain rating and share in the opera van java program in trance 7. The qualitative research methodology with morrisan theory is to analyze the results in theory and to fully explain industry competition to influence the audience with triangulation, interview and observation techniques. The conclusion of applying the SWOT theory model is about the strengths and weaknesses of the opera van java program on the company's internal conditions and about the opportunities and threats facing the company.